Reflection on Students' Competence and Challenges in Achieving Digital Media Literacy in English Learning - Menggo, Sebastianus (IJEE (INDONESIAN JOURNAL OF ENGLISH EDUCATION), 2024)
This study aims to investigate and disclose the students' profiles and the obstacles that stand in the way of obtaining digital media literacy in English instruction for high school students in Ruteng City, Indonesia. This study surveyed 595 students from six Senior High Schools in Ruteng City, Indonesia. The questionnaire served as the primary instrument for data collection, followed by quantitative and qualitative analysis of the findings. The study results indicated that the level of media literacy competence among students falls into the low category (2,84). This category was indicated by eight statements of media digital literacy competence. Moreover, five factors challenged the respondents' digital media literacy achievement, namely lack of students' enthusiasm and initiative in regards to digital media literacy (61,59%), lack of cost for purchasing internet data packages (71,20%), insufficient time allocated for the use of specific English learning software (59,48%), unstable internet network connectivity (58,27%), and lack of available ICT infrastructure in schools (58,33%). Various issues hinder the level at which students might acquire digital media literacy skills, and stakeholders are encouraged to address or overcome these obstacles.